Reductive transformation of V(iii) precursors into vanadium(ii) oxide nanowires. Issue 19 (4th May 2018) - Ojelere, Olusola; Graf, David; Ludwig, Tim; Vogt, Nicholas; Klein, Axel; Mathur, Sanjay
Abstract : This work shows the controlled reductive transformation of tailored V(iii ) precursors into metastable vanadium(ii ) oxide nanowires. Abstract : Vanadium(ii ) oxide nanostructures are promising materials for supercapacitors and electrocatalysis because of their excellent electrochemical properties and high surface area. In this study, new homoleptic vanadium(iii ) complexes with bi-dentate O, N-chelating heteroarylalkenol ligands (DmoxCHCOCF3, PyCHCOCF3 and PyNCOCF3 ) were synthesized and successfully transformed by reductive conversion into VO nanowires. The chemical identity of V(iii ) complexes and their redox behaviour were unambiguously established by single crystal X-ray diffraction studies, cyclic voltammetry, spectrometric studies and DFT calculations. Transformation into the metastable VO phase was verified by powder X-ray diffraction and thermo-gravimetry. Transmission electron microscopy and X-ray photoelectron spectroscopy data confirmed the morphology and chemical composition of VO nanostructures, respectively.